Bridging the skill gap between the acquired university curriculum and the requirements of the job market: A data-driven analysis of scientific literature - Naif Radi Aljohani; Ahtisham Aslam; Alaa O. Khadidos; Saeed Ul-Hassan (Journal of Innovation & Knowledge (JIK), 2022)
This research provides a comprehensive, first-of-its-kind, in-depth, data-driven analysis of the discussions on 'curriculum alignment' in the light of 'learned skills' and 'acquired skills', as illustrated by cross-disciplinary records in Scopus. It was undertaken from 2010 to 2021 on 10,214 data points obtained to fully grasp the issues, names and themes that have contributed to the field over the past decade, and it presents the case for the increased value and new application of bibliometric analyses. When faced with scholarly research not included in Scopus, on the one hand, and links between previously divided research groups, on the other, ensuring the compatibility of the various scientific information archives is essential. Only in this manner can the research artefacts be made evident, the concerns and problems that have been either overlooked or under-researched be identified, and practical debate between academia and policymakers be facilitated.
Keywords: 650; Acquired skill; Big data analytics; Higher education; Job market; Required skill; Skill gap; University curriculum; Upskill